LDL-Based Lipid Nanoparticle Derived for Blood Plasma Accumulates Preferentially in Atherosclerotic Plaque - Boada, Christian A.; Zinger, Assaf; Rohen, Scott; Martinez, Jonathan O.; Evangelopoulos, Michael; Molinaro, Roberto; Lu, Madeleine; Villarreal-Leal, Ramiro Alejandro; Giordano, Federica; Sushnitha, Manuela; De Rosa, Enrica; Simonsen, Jens B.; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Apolipoprotein-based drug delivery is a promising approach to develop safe nanoparticles capable of targeted drug delivery for various diseases. In this work, we have synthesized a lipid-based nanoparticle (NPs) that we have called “Aposomes” presenting native apolipoprotein B-100 (apoB-100), the primary protein present in Low-Density Lipoproteins (LDL) on its surface. The aposomes were synthesized from LDL isolated from blood plasma using a microfluidic approach. The synthesized aposomes had a diameter of 91 ± 4 nm and a neutral surface charge of 0.7 mV ± mV. Protein analysis using western blot and flow cytometry confirmed the presence of apoB-100 on the nanoparticle’s surface. Furthermore, Aposomes retained liposomes’ drug loading capabilities, demonstrating a prolonged release curve with ∼80% cargo release at 4 hours. Considering the natural tropism of LDL towards the atherosclerotic plaques, we evaluated the biological properties of aposomes in a mouse model of advanced atherosclerosis. We observed a ∼20-fold increase in targeting of plaques when comparing aposomes to control liposomes. Additionally, aposomes presented a favorable biocompatibility profile that showed no deviation from typical values in liver toxicity markers (i.e., LDH, ALT, AST, Cholesterol). The results of this study demonstrate the possibilities of using apolipoprotein-based approaches to create nanoparticles with active targeting capabilities and could be the basis for future cardiovascular therapies.